Molecular cloning, expression and mapping of the translational initiation factor elF1 gene in Oryza sativa - Rangan, Latha; Rout, Anusuya; Sudarshan, Medhavi; Gregorio, Glenn (Commonwealth Scientific and Industrial Research Organisation, 2009)
Protein translation is very sensitive to salt stress and the proteins involved in this process may be an important determinant of salt tolerance. We isolated a rice cDNA clone (OseIF1) from a salt-tolerant indica cultivar (Pokkali) subjected to 150 mm NaCl, the deduced amino acid sequence of which had homology with the Sui1 suppressor locus in Saccharomyces cerevisiaei Hansen. The sequence contains 753 bp with an open-reading frame of 345 bp and shares similarity with the sequences of Sui1 and eIF1 in plants and mammals. Southern analysis indicates that the gene is present in more than a single copy per haploid genome and mapped to chromosome 1 of rice. Expression of the gene was increased by salt stress and also upregulated after exogenous ABA and mannitol treatments, suggesting that its induction is related to the water-deficit effect of high salt.